Tri‐band filter using combined E‐type resonators. Issue 3 (1st January 2013) - Fan, W.X.; Li, Z.P.; Gong, S.X.
Abstract : A compact microstrip tri‐band bandpass filter using novel combined E‐type resonators (CETRs) is presented. The CETR consists of a quarter‐wavelength (λ/4) stepped‐impedance resonator (SIR) and a quarter‐wavelength (λ/4) unit impedance resonator through a via‐hole. These two components are relatively independent. The first and the third passband centre frequencies can be flexibly controlled by tuning the impedance ratio RZ of the SIR, whereas the second passband frequency is fixed. The centre frequency of the second passband can be independently controlled by tuning the lengths of L2 . The filter is designed to operate at 1.95, 5.2, and 3.5 GHz. The simulated and measured results show good agreement.